Spirit's key - Cohn, Edith (Square Fish, 2016)
Having finally developed the psychic ability her father has used to provide for them, twelve-year-old Spirit Holden, aided by the ghost of her beloved dog Sky, investigates the mystery of why wild dogs are dying on their remote island.